Search for a common baryon source in high-multiplicity pp collisions at the LHC - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; López, Jorge; Martin, Nicole Alice; Pachmayer, Yvonne C.; et al. (Physics letters, 2020)
We report on the measurement of the size of the particle-emitting source from two-baryon correlations with ALICE in high-multiplicity pp collisions at s=13 TeV. The source radius is studied with low relative momentum p-p, p‾-p‾, p-Λ , and p‾-Λ‾ pairs as a function of the pair transverse mass mT considering for the first time in a quantitative way the effect of strong resonance decays. After correcting for this effect, the radii extracted for pairs of different particle species agree. This indicates that protons, antiprotons, Λ s, and Λ‾ s originate from the same source. Within the measured mT range (1.1-2.2) GeV/c2the invariant radius of this common source varies between 1.3 and 0.85 fm. These results provide a precise reference for studies of the strong hadron-hadron interactions and for the investigation of collective properties in small colliding systems.
ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, M.K. Köhler, J.A. Lopez, N.A. Martin, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, M. Schmidt, N.V. Schmidt, J. Stachel, S.F. Stiefelmaier, B. Windelband, A. Yuncu [und viele weitere]
Gesehen am 10.03.2021